Commuting stress among workers in Jabodetabek and its impact on health - Shofi Nadia; Maryam Abidah Masykuroh; Wahyu Dwi Admadja; Daeng Azizah Rahmatia; Nurani Fitriyah; Fivi Nurwianti (Jurnal Psikologi Tabularasa, 2025)
Millions of commuters travel to and from Jabodetabek daily, facing traffic congestion and overcrowding in public transportation. Previous studies have shown that commuting stress has various negative effects on individuals. This study aims to examine the commuting stress experienced by workers in Jabodetabek and its impact on sleep quality and self-rated health. Data were collected cross-sectionally using self-report questionnaires, with 113 Jabodetabek commuters participating in the study. Linear regression analysis revealed that commuting stress had a significant negative effect on self-rated health (β = -0.534, p < 0.001) and sleep quality (β = -0.312, p < 0.001). Additionally, travel duration was found to be positively correlated with commuting stress. Beyond its theoretical contributions, this study offers practical implications for companies in considering remote work strategies and for the government in emphasizing the importance of improving the quality and availability of public transportation.